Exploring relationships between pre-service teachers’ self-efficacy for writing and instruction provided in simulated elementary writing conferences - Gillespie Rouse, Amy; Young, Murphy K.; Gifford, Diane (Frontiers in Psychology, 2023)
Practice-based opportunities, like teaching simulations, are becoming more prevalent in teacher preparation programs. We sought to examine the instructional moves of 5 pre-service teachers during a simulated elementary writing conference using Mursion technology, a mixed-reality simulation (MRS) that emulates a classroom environment with student avatars. We examined both participants’ self-efficacy and their instructional moves during MRS writing conferences. To better understand pre-service teachers’ learning, we also examined reflections they wrote about their MRS experience. Results showed that pre-service teachers spent much of their time (31.7%) managing the environment (e.g., setting expectations, addressing student behavior) during MRS writing conferences, followed by nearly one-fourth of their time (24.2%) instructing students on their writing pieces (e.g., adding details, revising, editing), with high levels of teacher talk compared to student talk. Participants’ self-efficacy for writing, for teaching writing elements, and for writing instruction were not clearly related to their instructional moves during the MRS experience. However, participants’ reflections suggest that pre-service teachers felt the experience gave them the opportunity to practice making in-the-moment decisions and learn from their peers in a way that may allow them to have a more accurate understanding of their abilities to teach writing. Implications from these findings related to teacher self-efficacy, motivation, and teacher preparation programs are presented.